Identifikasi bentuk-bentuk guntingan dan jatuhan pencak silat kategori ganda - Aryan Baya Aprilyanto; Kurniati Rahayuni (Physical Education Departement of University PGRI Jombang, 2025)
In the sport of pencak silat there is a double category where this category is played by 2 (two) fighters by demonstrating techniques such as scissors and falls. One of the important assessments in the double category is the richness of techniques such as scissors and falls, so it is necessary to identify scissors and fall techniques to find out recommendations for techniques that are considered important to be used in making pencak silat choreography. This research method uses a quantitative descriptive method, as data processing with the stages of data reduction, data presentation, and conclusion drawing. In this study there are 47 videos of pencak silat double athlete matches at regional to international level championships held in Jakarta, Tangerang, Malang, Aceh. The results of the findings have been known there are 4 cutout techniques and 10 fall techniques, among these techniques there is 1 cutout and fall technique that is very often used, namely the neck cutout technique (GL), namely 38 movements with a percentage of 51% of the total. And the fall technique with a hand pull fall (JTT) is 72 movements with a percentage of 38% of the total number of fall techniques. The results of this study can be used as a reference or reference for the preparation of double choreography of pencak silat.